The digestive & urinary systems - Creative Media Applications (Westport, CT : Greenwood Press, 2003)
Examines the basic anatomy of the digestive and urinary systems; looks at their structure and function; describes the medical conditions--both environmental and otherwise--that can affect them; and offers tips on how to keep the body healthy.
Includes bibliographical references (p. 129) and index.
5-8
Keywords: Human physiology -- Juvenile literature; Environmental health; Human physiology; Environmental health; Physiology